The Relationship of Diabetes Mellitus Management Compliance with Diabetic Neuropathy in Diabetes Mellitus Patients - Pratiwi, Endhika Agustin; Purwanti, Okti Sri (Indonesian Journal of Global Health Research, 2024)
The increase in cases of diabetes mellitus requires serious treatment, people with DM must comply with self-management so that other disease complications do not arise which will make the situation worse. Self-management is an individual's actions based on his desires with the aim of controlling his illness. Diabetes self-management is the patient's involvement and responsibility for the management of DM which affects several physical aspects, diet management, blood sugar control, and compliance with taking medication which greatly influences the survival of people with DM. Objective to determine the relationship between compliance with diabetes management and the incidence of diabetic neuropathy in diabetes mellitus sufferers at RSUD Dr. Soehadi Prijonegoro Sragen. This research uses quantitative methods with a cross sectional approach. The population in this study were all diabetes mellitus sufferers at RSUD Dr. Soehadi Prijonegoro Sragen in January-November 2023 with a total of 1565 patients. The sample in this study consisted of 66 diabetes mellitus patients who were selected using purposive sampling techniques. Data collection was carried out using the Diabetes Self-Management Questionnaire (DSMQ) and observation sheets. The data analysis test in this study used a univariate test and a bivariate test using the chi square test. The majority of diabetes mellitus sufferers who were respondents in this study were female with the majority aged > 60 years, had a high school education level and had suffered from diabetes mellitus for a period of between 6-10 years. The majority of respondents in this study had compliance with diabetes management. The number of diabetes mellitus sufferers who experience diabetic neuropathy is the same as the number of diabetes mellitus sufferers who do not experience diabetic neuropathy. There is a significant relationship between compliance with diabetes management and the incidence of diabetic neuropathy in diabetes mellitus sufferers at RSUD Dr. Soehadi Prijonegoro Sragen with a p-value of 0.000 (P<0.05). There is a significant relationship between diabetes management compliance and the incidence of diabetic neuropathy in diabetes mellitus sufferers at Dr. Soehadi Prijonegoro Hospital, Sragen.